(untitled) (Educational Knowledge, 2020)
Education is a complex process increasingly influenced by innovative methodologies and other aspects related to teacher training. This research was conducted in five schools across the country. The sample consisted of five teachers and 154 students from the third cycle of basic education. Data was collected using interviews, focus groups, and observation. Several challenges were identified during the diagnostic phase: improving linguistic competence, systematizing the proper use of the school garden, enhancing comprehension of literary works, and systematizing integrative activities. Each of these challenges was addressed in the classroom for one month using action research methodology. The following innovative techniques were applied within the study, depending on the specific needs of each school: Thinking Routines; a Guide for the School Garden; a Guide for Reading Comprehension; a Guide for Integrative Activities; and the Flipped Learning Methodology. Subsequently, during the observation period, the impact of the implemented strategies was evaluated to verify the changes made by the teachers in their professional practice. The main result found was that, by using innovative methodologies, there was a positive impact on the construction of meaningful learning; increasing student participation in the teaching-learning process.